KEMAMPUAN KOMUNIKASI MATEMATIS TERHADAP MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE PADA PESERTA DIDIK KELAS XI FASE F SMA NEGERI 3 PADANG - Oktavia, Intan (Departemen Matematika, 2023)
Students learning mathematics need effective mathematical communication abilities. This skill is weak in class XI Phase F SMA Negeri 3 Padang 2023/2024. Evidenced by observations. Think Pair Square (TPSq) cooperative learning is being used. This study analyzes whether the TPSq model improves mathematical communication abilities over direct learning and how they evolve. Study employed Nonequivalent Posttest-Only Control Group Design. A quiz and final test assessed math communication. Sampling was random. The research hypothesis was supported by Mann-Whitney. Quiz data revealed all indicators improved. The P-value was 0.001. H0 was rejected due to a P-value < α=0.05. The TPSq model improves mathematical communication better.Keywords–Mathematical Communication Skills, TPSq, Direct Learning